ANALISIS RATA-RATA LINTASAN REDAMAN MODEL PROPAGASI PADA LAYANAN BASE TRANSEIVER STATION (BTS) BERSAMA AREA KOTA PONTIANAK - ., Rudi Sartino (Faculty of Engineering, Universitas Tanjungpura, 2017)
Selecting a good propagation model is quite difficult for a wireless communication design. In this study, an approach to calculate propagation attenuation circuit which was appropriate with characteristics in Pontianak area was done by a means of applying certain formula, for instance through Okumura-Hatta model and Walfisch-Ikegami model. This study aims at identifying the influence of antenna’s beam distance and signal reception at Mobile Station (MS) towards attenuation value, implementing Okumura-Hatta model and Walfisch-Ikegami model, and analyzing the average value of propagation attenuation circuit on Collective BTS (Base Transceiver Station) service in Pontianak. Based on the measurement, calculation, and analysis which was done in Jalan Husain Hamzah RT.05/RW.01 Kelurahan Paal Lima, Kecamatan Pontianak Barat, it was revealed that the average values of attenuation circuit for Telkomsel by distance 0.75 Km, 1.5 Km, 2.25 Km using Okumura-Hatta model were 125.42 dB, 142.58 dB, and 153.24 dB, with receptivity averages were - 85.42 dBm, -102.58 dBm, and -113.24 dBm. In Walfisch-Ikegami propagation model, the average value of attenuation circuit were 136.23 dB, 149.06 dB, 154.80 dB, with receptivity averages reached –96.23 dBm, -109.06 dBm, and -114.80 dBm. Meanwhile, for Three provider by distance 0.75 Km, 1.5 Km, and 2.25 Km using Okumura-Hatta model, it was obtained an average value of attenuation circuit as much as 124.31 dB, 141.99 dB, and 152.98 dB with receptivity averages were –84.01 dBm, -101.69 dBm, and -112.98 dBm. In Walfisch-Ikegami model, the average value of attenuation circuit were 135.80 dB, 146.52 dB, and 153.77 dB, with receptivity averages as much as –95.50 dBm, -106.22 dBm, -113.47 dBm. Key words: Attenuation propagation, RSCP, Okumura-Hatta, Walfisch-Ikegami